Candiduria: its characterization, antifungal susceptibility pattern and biofilm formation - Prakash, Ved; Verma, Deepika; Agarwal, Sumit (International Journal of Research in Medical Sciences, 2018)
Background: Candida are the fourth most common species causing urinary tract infections. The last two decades has shown rapid increase in Candida associated UTI along with change in its distribution. The indiscriminate use of antifungal drugs, especially azole group have contributed in emergence of resistant strains of Candida. Biofilm producing property of Candida also contributes to antifungal resistance. Aims and objectives was to detect the occurrence of Candida as causative agent of UTI and a potent bio film producer. The susceptibility of Candida to antifungal drugs and their correlation with the production of bio film and presence of Foleys catheter was also determined. Methods: A total of 4192 urine specimens were analysed. Candida species isolated from urine samples were characterized using CHROM agar, sugar assimilation tests and micro morphology on corn meal agar. The antifungal susceptibility testing was performed by modified disc diffusion method on MHA with two drugs; fluconazole 25µg, and voriconazole 1µg discs. The biofilm production capability was tested according to the protocol proposed by Branchini et al. Results: Out of 113 Candida species isolated, 16.8% were Candida albicans as compared to 83.2% non albicans, with Candida tropicalis as the most common species. Antimicrobial sensitivity by modified Kirby Bauer disc diffusion method showed 74.3 % of Candida isolates to be fluconazole sensitive while sensitivity to voriconazole was 100%. 60.2% of Candida were biofilm producers out of which 48.5 % were from urine samples of catheterized patients. Similarly, 26.4 % of fluconazole resistant strains were also biofilm producers. Conclusions: The increased incidence of Non albicans candiduria which are also biofilm producers and resistant to commonly used drug fluconazole is a matter of concern. Therefore, the species identification of Candida isolates along with their antifungal susceptibility pattern should be routinely performed to help the clinicians in better treating the patients with candiduria.